Spying in multi-market oligopolies - Pascal Billand; Christophe Bravard; Subhadip Chakrabarti; Sudipta Sarangi (Fondazione Eni Enrico Mattei (FEEM), 2010)
We consider a multimarket framework where a set of firms compete on two interrelated oligopolistic markets. Prior to competing in these markets, firms can spy on others in order to increase the quality of their product. We characterize the equilibrium espionage networks and networks that maximize social welfare under the most interesting scenario of diseconomies of scope. We find that in some situations firms may refrain from spying even if it is costless. Moreover, even though spying leads to increased product quality, there exist situations where it is detrimental to both consumer welfare and social welfare.
Keywords: C70; L13; L20; 330; Oligopoly; Multimarket; Networks